2010
DOI: 10.1093/nar/gkq264
|View full text |Cite
|
Sign up to set email alerts
|

TOR-dependent reduction in the expression level of Rrn3p lowers the activity of the yeast RNA Pol I machinery, but does not account for the strong inhibition of rRNA production

Abstract: Ribosome biogenesis is tightly linked to cellular growth. A crucial step in the regulation of ribosomal RNA (rRNA) gene transcription is the formation of the complex between RNA polymerase I (Pol I) and the Pol I-dependent transcription factor Rrn3p. We found that TOR inactivation leads to proteasome-dependent degradation of Rrn3p and a strong reduction in initiation competent Pol I–Rrn3p complexes affecting yeast rRNA gene transcription. Using a mutant expressing non-degradable Rrn3p or a strain in which defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 53 publications
6
56
1
Order By: Relevance
“…The latter scenario is plausible since overexpression of wild-type Rrn3 was sufficient to increase rRNA synthesis under certain conditions in yeast and Drosophila [48,52]. In our study, however overexpression of Rrn3 enhanced Pol I transcription initiation, but it was unable to promote full-length rRNA production most likely because elongation or processes coupled to elongation such as processing become…”
Section: Accepted Manuscript 19contrasting
confidence: 48%
See 1 more Smart Citation
“…The latter scenario is plausible since overexpression of wild-type Rrn3 was sufficient to increase rRNA synthesis under certain conditions in yeast and Drosophila [48,52]. In our study, however overexpression of Rrn3 enhanced Pol I transcription initiation, but it was unable to promote full-length rRNA production most likely because elongation or processes coupled to elongation such as processing become…”
Section: Accepted Manuscript 19contrasting
confidence: 48%
“…On the other hand, in yeast cells TOR inactivation resulted in proteasomedependent degradation of Rrn3p and a strong reduction in Pol I transcription initiation [48]. Indeed, we found that serum withdrawal led to significant reduction in Rrn3 protein abundance within 30min (Fig 6A).…”
Section: Overexpression Of Rrn3 and Increased Pol I Transcription Inimentioning
confidence: 73%
“…Since then, various studies have explored the molecular mechanism underlying this observation. It could be shown that the amount of initiation-competent complex of RNA Pol I with the essential transcription factor Rrn3 is reduced in rapamycin-treated cells (11,56). This observation correlated well with a reduced RNA Pol I association with the rRNA gene locus under these conditions (11,56).…”
mentioning
confidence: 79%
“…Blot analysis and quantitation were performed as described elsewhere (52,56). For Northern blot analysis membranes were hybridized with a 32 P-labeled 25S oligonucleotide probe (probe 212, 5Ј-CTC CGC TTA TTG ATA TGC-3Ј).…”
Section: Methodsmentioning
confidence: 99%
“…When detached from DNA, free monomeric Pol I cannot directly be recruited to rDNA promoters but requires prior binding to the activating factor Rrn3 [12,13]. This event allows direct downregulation of rRNA production by Rrn3 degradation [24,30]. In addition, rDNA transcription is also down-tuned by Pol I dimerization [24].…”
Section: Pol I Enzyme Activationmentioning
confidence: 99%